Pengaruh Terpaan Web Series Tropicana Slim ‘Sore’ pada Behavioral Intention - Ratih Pandu Mustikasari (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2018)
Web series as a new form to deliver the message become alternative for company to promote their product. There are few company which create web series to build their company image. Web series also become the new way form of sponsorship. It’s happened based on the development of active audience in choosing media content, there for the emergence of web series as new form of sponsorship can reduce audience activity who love to skip the commercial break. “Sore” is one of the web series tittle which created by Tropicana Slim as sponsorship form. Tropicana Slim create “Sore” to get closer with their market, young adult. Web series that used as sponsorship become interesting subject tobe studied, because there is only some research that use web series as a subject. This research will use Reasoned Action Theory (RAT) to see the influence of web series exposure toward the behavioral intention especially in the brand purchase intention and the tendency of healthy living behavior. Methods of data collection is done by survey and calculation model is done by path analysis. The result of this research shows that web series has no effect on brand purchase intention or the trend of healthy living behavior directly. The influence come when the responded motivate by their social environment that has been mentioned in RAT.